The Domestication Makeup: Evolution, Survival, and Challenges - Ahmad, Hafiz Ishfaq; Ahmad, Muhammad Jamil; Jabbir, Farwa; Ahmar, Sunny; Ahmad, Nisar; Elokil, Abdelmotaleb A.; Chen, Jinping (Frontiers in Ecology and Evolution, 2020)
Animal domestication is considered a complex and multistage process that altered phenotypically and physiologically the domesticates relative to their wild ancestors. Domestication has been the focus of several studies from different specialties. Studying when, where, and how domestication happened is essential to understand the origins of civilizations and the evolution of domesticated species. The development of both humans and domestic animals is hard to magnify, and the genetic variations that occurred during the early animal domestication process remain vague. Once domestication occurred, several events as gene flow and selective pressures occurred, leading to genomic and phenotypic alterations. In this review, we discuss the current knowledge about the spatiotemporal outlines of domestication and debates surrounding the intent, speed, and evolutionary landscapes of this event. We also focus on the core challenges for future research. In conclusion, we argue that although the current growth has been remarkable, the next era will produce even more significant insights into not only how domestication occurred but also where and when it did so.